2018
DOI: 10.1007/s11573-018-0897-5
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating acceptance of emerging technologies using twitter: the case of self-driving cars

Abstract: In an early stage of developing emerging technologies, there is often great uncertainty regarding their future success. Companies can reduce this uncertainty by listening to the voice of customers as the customer eventually decides to accept an emerging technology or not. We show that risk and benefit perceptions are central determinants of acceptance of emerging technologies. We present an analysis of risk and benefit perception of self-driving cars from March 2015 until October 2016. In this period, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…In line with Kohl et al (2018) and Raue et al 2019, we argue that the perception of risks and benefits are important factors predicting AVA. Similar to Milakis, Van Arem, and Van Wee (2017) in their ripple effect of automated driving model, the moral-normative perception of risks and benefits in our model represents higher-order implications of AVs on energy consumption, air pollution, economy, public health and social equity.…”
Section: Moral-normative Aspects Of Ava: Risk-benefit Perceptionsupporting
confidence: 89%
“…In line with Kohl et al (2018) and Raue et al 2019, we argue that the perception of risks and benefits are important factors predicting AVA. Similar to Milakis, Van Arem, and Van Wee (2017) in their ripple effect of automated driving model, the moral-normative perception of risks and benefits in our model represents higher-order implications of AVs on energy consumption, air pollution, economy, public health and social equity.…”
Section: Moral-normative Aspects Of Ava: Risk-benefit Perceptionsupporting
confidence: 89%
“…However, these issues might not have become salient in the public discourse. Kohl et al (2018) showed that on Twitter, the discussion around driverless vehicles typically centers around accidents involving self-driving cars, concerns for safety and privacy, and personal benefits such as saving time, with relatively little reference to this technology’s larger socioeconomic implications. Nevertheless, as self-driving cars enter the political discourse, future research should still track the influence of economic conservatism.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived benefits and perceived risks are the key determinants of public acceptance of, intention to use, and willingness to pay for, AVs [15,16,111,114], despite some existing contradictory reports regarding no contribution between perceived risks and intention to use AVs [114]. As for Payre et al, [82], such inconsistency stems from dissimilar AV deployment contexts-e.g., "different road types, driving environments, and/or physical/mental status" ([56], p.414).…”
mentioning
confidence: 99%